Formalization of digital transformation processes of the construction organization system - Dubinin, D; Novak, Ye. (Ways to Improve Construction Efficiency, 2025)
The article considers the issues of digital transformation of the construction organization system as a key direction for increasing the efficiency and competitiveness of the industry in the context of global challenges and the post-war recovery of Ukraine. It is emphasized that the transition to a digital economy requires not only the implementation of individual technological innovations, but also the systematic formalization of management processes, organizational structures and mechanisms of interaction between all participants in the investment and construction cycle.A scientific and methodological approach to the formalization of digital transformation processes is proposed, which is based on a combination of the principles of system analysis, qualimetry tools and models of organizational and economic management. Key areas of formalization are identified, including: description of business processes in digital form; creation of integrated information environments; unification of criteria and indicators of digital maturity efficiency; adaptation of management mechanisms to the conditions of the digital economy. Particular attention is paid to the use of BIM technologies, cloud services, automated resource management systems and digital platforms for transparent interaction between customers, contractors, project organizations and state regulators.The methodological principles of building a factor-criteria submodel for assessing the level of digital development of construction participants as a tool for diagnosing and managing transformation processes are disclosed. It is argued that the use of such a submodel allows for an objective assessment of the digital maturity of enterprises, identifying weaknesses in the implementation of technologies, determining strategic development directions and forming priorities for investing in digitalization.The practical significance of the study lies in the possibility of using the proposed approaches by state administration bodies, construction companies and investors to increase the transparency of management, the efficiency of project implementation and ensuring sustainable development of the construction sector.The results of the study contribute to the deepening of the scientific and methodological foundations of the digital transformation of construction and the formation of a modern model of industry organization that meets the requirements of the digital economy and the challenges of rebuilding Ukraine.